Evolution of Solar Photovoltaic Policies and Industry in China. Issue 2 (February 2021) - Zhang, Yueqi; Xie, Pengcheng; Huang, Ying; Liao, Cuiping; Zhao, Daiqing
Abstract: China has experienced a rapid growth of both SPV manufacturing capacity and installed capacity in the last twenty-five years. However, this growth has followed a very erratic path. This study identifies policies issued through this period for a closer look on the impact of these policies to the solar photovoltaic (SPV) industry development in China. This paper examines five stages in China's SPV policy from mid-1990s to 2019. Each stage has implemented different combinations of policy program. These changes in government policy and the effects to the SPV sector are attributed to three main sets of variables. First and foremost, the events that influence the policy and strategy priorities of Chinese government. Secondary factors include the government's poor management of the policy impacts to the SPV manufacturing industry and the domestic SPV market at early days, as well as policymaking and problems coping within government. The subsidy, FIT policies and other programs had stimulated the deployment of SPV in a large scale but brings several problems such as subsidy reliance. The fundamental measure to improve SPV development into a grid parity era is the technological advancement of photovoltaic in efficiency and manufacturing.